A Case Study in Low Aerosol Number Concentrations Over the Eastern North Atlantic: Implications for Pristine Conditions in the Remote Marine Boundary Layer. Issue 22 (28th November 2017) - Pennypacker, Sam; Wood, Robert
Abstract: We present a case study (20 September to 13 October 2015) of synergistic, multi‐instrument observations of aerosols, clouds, and the marine boundary layer (MBL) at the Eastern North Atlantic (ENA) Atmospheric Radiation Measurement site centered on a period of exceptionally low (20–50 cm −3 ) surface accumulation mode (0.1–1 μm) aerosol particle number concentrations. We divide the case study into three regimes (high, clean, and ultraclean) based on daily median number concentrations and compare finer resolution (hourly or less) observations between these regimes. The analysis focuses on the possibility of using these ultraclean events to study pristine conditions in the remote MBL, as well as examining evidence for a recently proposed conceptual model for the large‐scale depletion of cloud condensation nuclei‐sized particles in postfrontal air masses. Relative to the high and clean regimes, the ultraclean regime tends to exhibit significantly fewer particles between 0.1 and 0.4 μm in diameter and a relatively increased prevalence of larger accumulation mode particles. In addition, supermicron particles tend to dominate total scattering in the ultraclean regime, and there is little evidence for absorbing aerosol. These observations are more in‐line with a heavily scavenged but natural marine aerosol population and minimal contribution from continental sources such as anthropogenic pollution, biomass burning, or dust. The air masses with the consistently lowest accumulation mode aerosol number concentrations are largely dominated by heavily drizzling clouds with high liquid water path cores, deep decoupled boundary layers, open cellular organization, and notable surface forcing of subcloud turbulence, even at night. Key Points: Exceptionally low aerosol number at ENA ARM site is accompanied by a shift toward larger particle size within the accumulation mode Aerosol optical properties, CO concentrations, and back trajectories suggest ultraclean regime dominated by scavenged natural marine aerosol population Observations support model of low aerosol events driven by coalescence scavenging in postfrontal boundary layer clouds